الأخطاء الشائعة في الرياضيات لدي تلاميذ سنة الثالثة ابتدائي - صفاف,فريدة; حسيني.محمد أبو القاسم (University of Eloued جامعة الوادي, 2024)
ملخص: سعت هذه الدراسة إلى الكشف عن الأخطاء الشائعة في مادة الرياضيات لدى تلاميذ سنة الثالثة إبتدائي ومعرفة طبيعة هذه الأخطاء، لذلك تم الإعتماد على نتائج التلاميذ في اختبار التحصيلي لثلاثي الأول في مادة الرياضيات وكذلك اختبار تشخيصي للأخطاء في الرياضيات من إعداد الباحثة. وقد دلت عملية تحليل النتائج باستخدام أسلوب الوصفي التحليلي لرصد الأخطاء الشائعة في الرياضيات لدى تلاميذ سنة الثالثة إبتدائي وأن هؤلاء التلاميذ يرتكبون أخطاء في الرياضيات متنوعة والتي تمحورت في: أخطاء شائعة في المسائل الحسابية ومتمثلة في (عدم فهم المطلوب من الوضعية طرح بالاستعانة، الجمع، التحويلات خاصة في السعات وحساب الأطوال، علاوة عن الأخطاء في المقارنة بين المسافات). والأخطاء الشائعة في المفاهيم الهندسية تمثلت في:(عدم القدرة التلميذ على رسم قطعة مستقيمة مع تحديد منتصفها، عدم قدرتهم على تميز بين التعامد والتوازي إلى جانب أخطاء في فهم المفاهيم الرياضية. الهندسية واستخدام الوسائل الهندسية).Abstract: This study sought to detect common errors in mathematics among students of the third year of primary school and to know the nature of these errors, so the results of students were relied on in the achievement test for the first triple in mathematics as well as the diagnostic test for errors in mathematics prepared by the researcher. The process of analyzing the results was indicated by the use of the descriptive analytical method to monitor common errors in mathematics among students of the third year of primary school and that these students commit various errors in mathematics, which centered on: common errors in arithmetic problems represented in (lack of understanding of the required position subtraction by help, addition, transformations, especially in amplitudes and calculating lengths, in addition to errors in comparing distances). The common mistakes in geometric concepts were: (the student's inability to draw a straight segment with the middle determined, their inability to distinguish between orthogonality and parallelism, as well as errors in understanding mathematical concepts
Keywords: رياضيات; أخطاء شائعة; common mistakes; mathematics; third year primary students